Memory illusions in chicken consumption: Thinking style relationship analysis - Tuğcu, Elçin Duygu; İnce Karaçeper, Ecem (Rahman Temizkan, 2025)
Research on memory, a focal point of numerous disciplines, is extensively documented in the literature, particularly concerning psychological processes and brain-behavior relationships. Beyond merely observing memory's functionality, it is crucial to scrutinize the phenomenon of memories that are misremembered or recalled as if they never occurred—processes characterized by errors, distortions, and reconstructions. Memory illusions involve the acceptance of semantically accurate yet structurally altered, unreal thoughts as genuine. To study these illusions, the Deese-Roediger-McDermott (DRM) paradigm—a widely adopted cognitive framework that conceptualizes memory as a network of nodes and their interconnections—is utilized. This research aims to explore memory illusions and false memories through the application of DRM lists, examining the intricate relationship between these phenomena, source memory, and individuals' thinking styles, as well as their implications for chicken consumption within the context of memory distortion.
Keywords: False Memory; Memory Illusion; DRM Paradigm; Chicken Consumption; Brain-Behaviour Relationships